Brachial plexus of the porcupine (Hystrix cristata) - Aydin, Ali (Czech Academy of Agricultural Sciences, 2003)
In this study, the brachial plexus of the porcupine (Hystrix cristata) was investigated. Four porcupines (two males and two females) were used and the brachial plexus of them were dissected. It was found that the brachial plexus of the porcupine was formed by rami ventralis of C5, C6, C7, C8, T1 and T2. The rami ventralis of C5 and T2 were divided into two branches. The caudal branch of C5 and cranial branch of T2 contributed to the brachial plexus. The caudal branch of C5 and C6 constituted the cranial trunk and the caudal trunk was formed by a branch which came from cranial trunk, rami ventralis of C7, C8, T1 and the cranial branch of ventral ramus of T2. Contribution of C5 and T2 to the formation of the brachial plexus and division of the brachial plexus to the caudal and cranial trunks differ the brachial plexus of this species from those of rat, mouse and mammals. © 2007 Veterinarni Medicina.
Keywords: Brachial plexus; Hystrix cristata; Porcupines; Spinal nerves